Magnetized vermiculite as a tool for the treatment of produced water generated by oil companies: Effects on aquatic organisms before and after treatment - Viana, Tais S.; Campos, Diana; Bartilotti, Mariana [UNESP]; Leite, Fernanda G.; Zanoni, Maria Valnice [UNESP]; Dorta, Daniel J.; Oliveira, Danielle P.; Pestana, João L. T. (Wiley, 2023)
Produced water (PW) generated by oil companies is a highly impacting waste that contains chemicals such as metals and organic and inorganic compounds. Given its polluting potential, PW requires effective treatment before being discharged into the environment. Conventional treatments have limited efficiency in removing PW toxicity, so alternative approaches must be developed and standardized. In this context, treatment with adsorbent materials like magnetized vermiculite (VMT-mag) is highlighted. This work aimed to evaluate the efficiency of treatment with VMT-mag in reducing PW toxicity to aquatic biota. For this purpose, three aquatic species (the midge Chironomus riparius, the planarian Girardia tigrina, and the crustacean Daphnia magna) were exposed to untreated PW and to PW treated with VMT-mag at laboratory conditions. The assessed endpoints included mortality, growth, emergence, and developmental time of C. riparius; mortality, locomotion, feeding, and head regeneration of G. tigrina; and intrinsic population growth rate (r) and reproductive output of D. magna. The results showed that all the species exposed to raw PW were impaired: C. riparius had delayed development, G. tigrina had reduced locomotor activity and delayed head regeneration, and D. magna had reduced reproduction and delayed intrinsic population growth rate (r). Most of the analyzed parameters showed that treatment with VMT-mag diminished PW toxicity. Therefore, using VMT-mag to treat PW may be the key to reducing the PW effects on aquatic organisms.
Keywords: freshwater invertebrates; petroleum extraction; produced water; sub-lethal effects; toxicity